2010
DOI: 10.1371/journal.pone.0009756
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Outbreak from Consuming Xanthium strumarium Seedlings during Time of Food Scarcity in Northeastern Bangladesh

Abstract: BackgroundAn outbreak characterized by vomiting and rapid progression to unconsciousness and death was reported in Sylhet Distrct in northeastern Bangladesh following destructive monsoon floods in November 2007.Methods and FindingsWe identified cases presenting to local hospitals and described their clinical signs and symptoms. We interviewed patients and their families to collect illness histories and generate hypotheses about exposures associated with disease. An epidemiological study was conducted in two ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…Hollman et al (1996) reported that the plant flavonoids had anti-inflammatory, anti-mutagenic and anti-allergic effects. However, adverse effects such as mutation, cancer, gastric problems and inflammatory disorders for some plant oils were reported (Qu et al 1992;Chiang et al 1997;Gurley et al 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hollman et al (1996) reported that the plant flavonoids had anti-inflammatory, anti-mutagenic and anti-allergic effects. However, adverse effects such as mutation, cancer, gastric problems and inflammatory disorders for some plant oils were reported (Qu et al 1992;Chiang et al 1997;Gurley et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the unconscious use of the plants in medicine could cause toxic (Qu et al 1992;Chiang et al 1997), mutagenic or cancerogenic effects (Gurley et al 2010;Háznagy-Radnai et al 2008;Rencuzogullari et al 2009;Buyukleyla and Rencuzogullari 2009;Kayraldiz et al 2010;Kocaman et al 2011). Azirak and Rencuzogullari (2008) also reported that thymol and carvacrol induced chromosomal abnormalities in bone marrow cells of rats.…”
Section: Introductionmentioning
confidence: 99%
“…During 2007, a fatal outbreak of illness occurred among villagers in Bangladesh when they consumed Xanthium strumarium seedlings (commonly known as cocklebur) after destructive monsoon flooding eliminated most of the available local food supply. 1 Consumption of large amounts of these seedlings resulted in nausea, vomiting, loss of consciousness, hepatotoxicity, and in some cases, death among villagers. 1 Epidemics of lathyrism and neurolathyrism, a condition resulting in irreversible spastic paraparesis (extremity weakness) of the lower limbs resulting from ingestion of the grasspea (Lathyrus sativus), have occurred throughout history in times of drought and food shortages.…”
Section: Introductionmentioning
confidence: 99%
“…1 Consumption of large amounts of these seedlings resulted in nausea, vomiting, loss of consciousness, hepatotoxicity, and in some cases, death among villagers. 1 Epidemics of lathyrism and neurolathyrism, a condition resulting in irreversible spastic paraparesis (extremity weakness) of the lower limbs resulting from ingestion of the grasspea (Lathyrus sativus), have occurred throughout history in times of drought and food shortages. 2,3 Konzo, a permanent spastic para-or tetraparesis, is reported to occur during dry seasons and is associated with consumption of improperly prepared cassava (Manihot esculenta).…”
Section: Introductionmentioning
confidence: 99%
“…Recently some toxic effects of Xanthium strumarium have been reported from Bangladesh. After consuming the seed and seedlings of X. strumarium, an outbreak including vomiting and unconsciousness occurred in the people of the northeastern part of Bangladesh in 2007, including some fatalities (Gurley et al 2010). Although both the forms were reported as poisonous at the seedling stage, the purple form is more toxic (Dr. Mohammed Zashim Uddin, personal communication).…”
mentioning
confidence: 99%